PENDAMPINGAN PELABELAN DAN PEMBUATAN WEBSITE UNTUK PEMASARAN PRODUK HASIL PENGOLAHAN SAMPAH DI TPS-3R KELURAHAN TALANG KELAPA KECAMATAN ALANG-ALANG LEBAR - Eka Sri Yusmartini; Mardwita Mardwita; Innike Abdillah Fahmi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Waste generated by households can have economic value using the 3R method by the TPS. TPS-3R of the Maju Jaya Self-Help Group (KSM) is a pilot TPS in household waste management in Talang Kelapa Village, Alang-alang Lebar Subdistrict. The products produced are compost, liquid organic fertilizer and handicrafts from used goods. The obstacle faced is ineffective and efficient marketing. This is due to not having the correct label and ineffective marketing. So that assistance is needed in making product labels to be attractive and training in making websites to expand the marketing of processed waste products from TPS-3R KSM Maju Jaya. From the results of this activity, TPS-3R KSM Maju Jaya was able to create a logo that presented the values of TPS-3R KSM Maju Jaya and produced a more attractive product label. In addition, TPS-3R Maju Jaya has a website to increase sales of its products.